Education Financing System in Indonesia (Integrated Merangin VHS Institution) - Yahya, Yahya; Hadiyanto, Hadiyanto; Wulandari, Diana (Postgraduate School, Universitas Negeri Padang, 2023)
Education is the initial capital to improve the quality of human resources themselves because with education it is hoped that humans will have high knowledge and skills. However, education cannot be separated from the cost of education itself. The Law (UU) No. 20/2003 concerning